(untitled) (Research, Society and Development, 2025)
The aim of this article is to deepen Mota & Brêtas’ analysis, in this Journal, in 2022, on the social representations of non-consensual pornography, having as its axis the founding confusion between being a subject and being an object. Based on this ontic-symbolic rupture, the text discusses the psychic effects of the colonization of the gaze and its reverberations in processes of revenge, domination and erasure of the Self. Based on authors from social psychology (Moscovici, Gagnon and Simon, Honneth, Gergen) and depth psychology (Jung, Hillman, Neumann), a hermeneutic and socio-historical interpretation of subjectivation as a journey is proposed: from the trauma of being an object to reconciliation with one’s own totality. The text articulates the theory of the Self with the need for a symbolic education that welcomes the contemporary subjective core of the wounded being. The method used is qualitative, based on hermeneutics and phenomenology, integrating intertextual, symbolic and cultural reading. The article is structured as a dialogue in continuity with the original article and proposes an integrative paradigm between social psychology, culture and self-care.